Diffusion of wireless applications. - Toshiya, Alexander Osawa. (2008)
The research reported here looks at the diffusion of wireless applications with the advent of 3G technology. Today, the most talked about mobile wireless data service is the phenomenally successful I-mode mobile Internet service in Japan. I-mode’s success has propelled DoCoMo into a global telecommunications role model.